Sec5, a member of the exocyst complex, mediates Drosophila embryo cellularization. - Murthy, M.; Teodoro, R.O.; Miller, T.P.; Schwarz, T.L. (Development, 2010)
Cellularization of the Drosophila embryo is the process by which a syncytium of approximately 6000 nuclei is subdivided into discrete cells. In order to individualize the cells, massive membrane addition needs to occur by a process that is not fully understood. The exocyst complex is required for some, but not all, forms of exocytosis and plays a role in directing vesicles to appropriate domains of the plasma membrane. Sec5 is a central component of this complex and we here report the isolation of a new allele of sec5 that has a temperature-sensitive phenotype. Using this allele, we investigated whether the exocyst complex is required for cellularization. Embryos from germline clones of the sec5(ts1) allele progress normally through cycle 13. At cellularization, however, cleavage furrows do not invaginate between nuclei and consequently cells do not form. A zygotically translated membrane protein, Neurotactin, is not inserted into the plasma membrane and instead accumulates in cytoplasmic puncta. During cellularization, Sec5 becomes concentrated at the apical end of the lateral membranes, which is likely to be the major site of membrane addition. Subsequently, Sec5 concentrates at the sub-apical complex, indicating a role for Sec5 in the polarized epithelium. Thus, the exocyst is necessary for, and is likely to direct, the polarized addition of new membrane during this form of cytokinesis.